Objective Accuracy Indicators of the Single-Joint Arm Movements Simultaneous Reproduction with Closed Eyes and under Visual Control in Patients with Hemiparesis and Healthy Test Subjects (a New Method for Proprioceptive Sensitivity Objective Assessment) - Pavlova, Olga G.; Roschin, Vadim Yu; Sidorova, Marina V.; Selionov, Victor A.; Nikolaev, Evgeniy A.; Khatkova, Svetlana E. (Bulletin of Rehabilitation Medicine, 2021)
Aim. We have developed a method for objective assessment of proprioceptive sensitivity (PS) based on determining the accuracy of reproduction with the eyes closed of the tested arm passive single-joint movements by active movements of the other arm during their execution. It was shown that healthy test subjects reproduce the passive movements with high accuracy, while post-stroke patients with hemiparesis reproduce a large proportion of paretic arm test movements with gross qualitative and quantitative errors. To make sure that the reproduction errors are associated with the state of PS but not with the cognitive factor or the functional state of the conditionally healthy arm, it was necessary to find out how accurately these patients are able to reproduce the test-movements under visual control. Materials and Methods. In 11 patients with a lesion in the right and in 9 patients in the left hemispheres of the brain and a control group of 23 healthy subjects, the accuracy of reproduction of the 5 elementary hand movements was studied: flexion-extension in the shoulder, elbow and wrist joints and abduction–adduction in the shoulder and wrist joints. The test person was subjected to a series of passive cyclic movements of the test hand during which he had to copy them with active movements of the other hand. The reproduction procedure for each test movement was performed first under visual control and then with the eyes closed. The angles in the test join and the same joint of the other arm were recorded. Qualitative and quantitative indicators were used to assess the degree of similarity of active and passive movements and to reveal the correspondence of copying accuracy to the previously developed conditional criterion of the norm (CCN) of PS in healthy test subjects. Results. It was shown that in healthy test subjects the accuracy of all movements copying in tests with closed eyes and 98% of movements in tests with opened eyes met the requirements of the CCN. In the group of patients in tests with eyes closed, copying only 61% of movements met this criterion. 20.4% of movements were reproduced with qualitative gross errors, 18.4% were copied qualitatively correctly but differed from CCN in quantitative indicators. In tests with visual tracking of passive movements, reproduction of 98% of movements was qualitatively correct and 83% of movements corresponded to CCN. Conclusions. The vast majority of single-articular movements of the paretic arm are copied by patients with unilateral brain damage under visual control qualitatively correctly and accurately (meeting the CCN). It means that in the course of the study of PS by the proposed method, they, as a rule, understand the motor task and can reproduce the tested movements with their conditionally healthy arm. From this it follows that the main cause of these movements impaired copying in tests with closed eyes is proprioceptive deficit.